Are Schools Truly Inept? A Reappraisal of the Most Controversial Report of our Time - Donald D. Chipman (Educational Considerations, 1975)
The "troubled times of popular education" is a topic that shows up just about every year. The Jencks' report, however, bolsters the standard criticisms with sophisticated statistical analyses. Does the Jencks' conclusion still stand that the teaching profession is incapable of making any constructive contribution to the education of the lower-class child?